The gene expression database for mouse development (GXD): Putting developmental expression information at your fingertips. Issue 10 (4th July 2014) - Smith, Constance M.; Finger, Jacqueline H.; Kadin, James A.; Richardson, Joel E.; Ringwald, Martin; Mansour, Suzanne L.; Ornitz, David M.
<x xml:space="preserve">Abstract</x> Because molecular mechanisms of development are extraordinarily complex, the understanding of these processes requires the integration of pertinent research data. Using the Gene Expression Database for Mouse Development (GXD) as an example, we illustrate the progress made toward this goal, and discuss relevant issues that apply to developmental databases and developmental research in general. Since its first release in 1998, GXD has served the scientific community by integrating multiple types of expression data from publications and electronic submissions and by making these data freely and widely available. Focusing on endogenous gene expression in wild‐type and mutant mice and covering data from RNA in situ hybridization, in situ reporter (knock‐in), immunohistochemistry, reverse transcriptase‐polymerase chain reaction, Northern blot, and Western blot experiments, the database has grown tremendously over the years in terms of data content and search utilities. Currently, GXD includes over 1.4 million annotated expression results and over 260, 000 images. All these data and images are readily accessible to many types of database searches. Here we describe the data and search tools of GXD; explain how to use the database most effectively; discuss how we acquire, curate, and integrate developmental expression information; and describe how the research community can help in this process. Developmental Dynamics 243:1176–1186, 2014. © 2014 The Authors Developmental Dynamics published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists.